The Designing About Job Descriptions at PT. Coco Agricultura Indonesia - Fadlan, Gilang Bagus (Jurnal Pengabdian Masyarakat, 2025)
Purpose: Conducting observations at PT. Coco Agricultura Indonesia will be the target for practical work output. The implementation process is carried out after conducting what is called an interview to find information related to the job description to be used as material for designing the Job Description. During the practical work process, implementers also carry out analysis related to company SOPs, employees who are disciplined and company targets. This is included in the output design process for implementers to know the types of employee job descriptions that are the responsibility and contribution of the company that is the target for practical work. Method: In preparing this practical work report, several methods were used. The methods used in collecting data are interviews and observations.  Practical Application: By implementing a detailed Job Description, it provides employees with a good basis for designing discipline and understanding tasks in working according to their respective duties so as to avoid confusion and discrepancies in following the updated Job Description. Conclusion: In the process of implementing the Job Description which has been carried out by the implementer of practical work activities (KP), this activity makes PT. Coco Agricultura Indonesia has experienced a number of changes and improvements in various operational aspects and understanding of work in terms of job descriptions. With this change, the establishment of clear performance standards and detailed evaluation criteria from Job Descriptions helps in measuring employee performance more objectively.